2013
DOI: 10.3748/wjg.v19.i28.4526
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder polyps: Factors affecting surgical decision

Abstract: The risk of malignancy was high in the patients over 50 years old who had single polyps with diameters > 10 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 21 publications
2
29
0
3
Order By: Relevance
“…To date, several factors such as advanced age, male gender, ethnicity, genetics, diabetes mellitus, hypertension, and obesity have been identified as risk factors associated with the occurrence of GBPs (2,3,7). Although there are conflicting reports about sex predominance and average age, two-third patients were female and the mean age was about 50 years in our study, similar to the majority of previous studies (8)(9)(10)(11). Further, a close relationship between fat metabolism and GBP formation has been reported in the literature (2).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To date, several factors such as advanced age, male gender, ethnicity, genetics, diabetes mellitus, hypertension, and obesity have been identified as risk factors associated with the occurrence of GBPs (2,3,7). Although there are conflicting reports about sex predominance and average age, two-third patients were female and the mean age was about 50 years in our study, similar to the majority of previous studies (8)(9)(10)(11). Further, a close relationship between fat metabolism and GBP formation has been reported in the literature (2).…”
Section: Discussionsupporting
confidence: 79%
“…1,13,14). However, a polyp size of 10 mm has been generally accepted as a surgical indication (4,8,16,17). In our study, size was found to be one of the independent factors of neoplastic GBPs.…”
Section: Discussionmentioning
confidence: 51%
“…The suggested predictive factors of a malignant GB polyp include size (≥10 mm), solitary lesion, age (≥50-60 years), increased size of polyp during follow-up, concurrent gallstones, sessile lesions, and gallbladder wall thickening [1,17,18]. In our study, the significant predictive factors of a Note: ROI = region of interest neoplastic polyp were age (≥57 years), size (≥15 mm), the absence of hyperechoic foci, an irregular margin, a sessile shape, a single polyp, and the presence of adjacent GB wall thickening by univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Phrygian cap anomaly by itself does not suggest invasive intervention, [2][3][4] but the suspicion of associated gallbladder polypsmay indicate the needfor surgical management. [7][8][9] The malignant potential of 10 mm polyps is high, but the smallerones must also be monitored. 6,8 Male patients older than 45 years presenting with gallbladder polyps10 mm or greater in diameter and gallbladder wall thickness greater than 5 mm should be considered at high risk of local cancer.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Male patients older than 45 years presenting with gallbladder polyps10 mm or greater in diameter and gallbladder wall thickness greater than 5 mm should be considered at high risk of local cancer. [7][8][9][10] Early-stage gallbladder cancer may be mistaken for benign polyps in imaging evaluations, 7 and this malignancy hasa poor prognosis because it may be asymptomatic until advanced stages. 6,9,10 normal.…”
Section: Introductionmentioning
confidence: 99%